Entrepreneurial orientation and performance of small and medium-sized enterprises: Mediating effects of differentiation strategy. Issue 5 (21st October 2019) - Shah, Syed Zulfiqar Ali; Ahmad, Maqsood
Abstract : Purpose: This paper aims to investigate the effects of entrepreneurial orientation (EO) on the performance of small and medium-sized enterprises (SMEs) with mediating role of differentiation strategy in Pakistan. Design/methodology/approach: A theoretical framework has been developed to base the hypotheses, as also to determine the exact approach in this study. To establish the influence of EO on the performance of SME, a five-point Likert scale questionnaire has been used to collect data from middle and senior managers who operate in SMEs in the manufacturing sectors. The sample illustrates 166 incumbents, comprising 68.07 per cent from middle management and 31.93 per cent from senior management operating in manufacturing sector of SMEs, by means of a stratified random sampling technique. The collected data were analyzed using SPSS and Amos graphics software. Hypotheses were tested by using structural equation modeling (SEM) technique. Findings: EO, as a whole, presents a significant positive effect on the performance of SMEs. Moreover, differentiation strategy partially mediated the relationship between EO and performance of SMEs. Two dimensions of EO, proactiveness and risk-taking propensity, strongly increased firm performance while innovativeness, competitive aggressiveness, autonomy and competitive energy did not cause any significant change. The findings differ from the current view of western enterprises that innovativeness (INO) played a major role by increasing performance of SMEs. The results transpired that innovativeness (INO) tends to reduce performance of SMEs, but the p -value did not reach a high significance value. Research limitations/implications: The main limitation of this empirical study is comparatively a small size of the sample. The analysis of power suggests that a larger sample could have provided more reliable and extensive results. Regardless of that, the analysis of reliability, using the Cronbach's alpha, exhibited the consistency of outcomes in providing an accurate portrait of the EO influences on the performance of SME. Practical implications: The study verifies that two dimensions of EO have considerable effects on the performance of SMEs, while the others have not, whereas, the EO, as whole, has significant positive effect on performance of SMEs. These findings should be helpful for researchers looking for appropriate performance measures, and for entrepreneurs aiming at getting support for their decisions and evaluating their performance. Originality/value: The current study appears to be first of its kind focusing on the link between EOs, as whole, and its dimensions, to performance of SMEs and differentiation strategies within the specific context of Pakistan.